Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Prado, Evandro P. [UNESP] (2024)
Nozzle type and droplet size are one of the most important factors that affect spray deposition and the efficacy of herbicides. This study focused on evaluating the performance of spray nozzles and droplet sizes on the deposition of glufosinate and its biological efficacy of two weed species. Treatments consisted of spraying glufosinate on Euphorbia heterophylla and Digitaria insularis by five spray nozzles (XR 11002 – fine droplet; TT 11002 – coarse; AIXR 11002 – very coarse; AIXR 110025 – extremely coarse; and TTI 11002 – ultra coarse) assessing the spray deposits and its influence on plant biomass reduction. The spray deposits on E. heterophylla were found to be similar between most of the spray nozzles, except for the TTI 11002 nozzle, which had lower spray deposits. In contrast, for D. insularis, the spray deposits tended to decrease as the droplet size increased. The spray uniformity was lower for the AIXR 11002 nozzle for E. heterophylla and the XR 11002 nozzle for D. insularis. Regarding the efficacy of glufosinate on both weeds, the lower C50 (concentration required for 50% dry weight reduction) were obtained using the XR 11002 nozzle with fine droplets. The TT 11002 nozzle and the AIXR 11002 nozzle showed intermediate C50, making them viable options to reduce spray drift and achieve acceptable weed control. However, the nozzles using extremely coarse (AIXR 110025) and ultra-coarse (TTI 11002) droplet class resulted in higher C50, indicating reduced herbicide efficacy. Our study provided clues on how different spray nozzles and droplet sizes can significantly impact spray deposits and herbicide efficacy on the control of E. heterophylla and D. insularis. Nozzles with fine droplet class generally provided better control, while extremely coarse and ultra-coarse showed reduced efficacy at weed control.